Performance Characteristics of Active Constrained Layer Damping - A. Baz; J. Ro (Shock and Vibration)
Theoretical and experimental performance characteristics of the new class of actively controlled constrained layer damping (ACLD) are presented. The ACLD consists of a viscoelastic damping layer sandwiched between two layers of piezoelectric sensor and actuator. The composite ACLD when bonded to a vibrating structure acts as a “smart” treatment whose shear deformation can be controlled and tuned to the structural response in order to enhance the energy dissipation mechanism and improve the vibration damping characteristics. Particular emphasis is placed on studying the performance of ACLD treatments that are provided with sensing layers of different spatial distributions. The effect of the modal weighting characteristics of these sensing layers on the broad band attenuation of the vibration of beams fully treated with the ACLD is presented theoretically and experimentally. The effect of varying the gains of a proportional and derivative controller and the operating temperature on the ACLD performance is determined for uniform and linearly varying sensors. Comparisons with the performance of conventional passive constrained layer damping are presented also. The results obtained emphasize the importance of modally shaping the sensor and demonstrate the excellent capabilities of the ACLD.